2012
DOI: 10.2337/dc11-2434
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Transition in Patients With Type 1 Diabetes

Abstract: OBJECTIVETo examine characteristics of the transition from pediatric to adult care in emerging adults with type 1 diabetes and evaluate associations between transition characteristics and glycemic control.RESEARCH DESIGN AND METHODSWe developed and mailed a survey to evaluate the transition process in emerging adults with type 1 diabetes, aged 22 to 30 years, receiving adult diabetes care at a single center. Current A1C data were obtained from the medical record.RESULTSThe response rate was 53% (258 of 484 eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
141
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(154 citation statements)
references
References 27 publications
11
141
1
1
Order By: Relevance
“…Providers reported a patient's level of maturity as the primary basis for transition and felt mastery of self-care behaviors was the most significant factor during the diabetes transition. This inclination is supported by Garvey and colleagues [5] who found individual patients' self-care proficiency more relevant to health outcomes than chronological age at the time of transition [5]. In our study, providers and patients agreed that learning how to manage insurance policies and the financial costs of diabetes in order to independently maintain self-care were the greatest challenges.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Providers reported a patient's level of maturity as the primary basis for transition and felt mastery of self-care behaviors was the most significant factor during the diabetes transition. This inclination is supported by Garvey and colleagues [5] who found individual patients' self-care proficiency more relevant to health outcomes than chronological age at the time of transition [5]. In our study, providers and patients agreed that learning how to manage insurance policies and the financial costs of diabetes in order to independently maintain self-care were the greatest challenges.…”
Section: Discussionsupporting
confidence: 70%
“…Unfortunately, studies report significant gaps in follow-up care and a decrease in physician visits after transferring from pediatric to adult care [4]. For instance, one study found 34% of patients reported a gap > 6 months between pediatric and adult diabetes care, resulting in greater risk for loss to follow-up care [5]. Other studies confirm a notable decrease in physician visits after transitioning to adult care and also report that fewer physician visits were associated with poor glycemic control [6,7].…”
Section: Background and Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Two articles reported results from the same study. 18,19 No additional articles were retrieved from searches of the reference lists of these 24 articles.…”
Section: Results Of the Searchmentioning
confidence: 99%
“…The goal of self-management is to maintain normalized blood glucose levels and avoid complications. Advances in technology and treatment options have significantly improved the longevity and health outcomes for people with T1D, yet despite advances in treatment and technology, young adults with diabetes are at risk for serious health threats such as microvascular complications, anxiety, depression, and gaps in clinical care [2,3]. The psychological impacts of diabetes resulting in depression, anxiety, and distress can negatively affect self-management and quality of life, especially for young people [4].…”
Section: Introductionmentioning
confidence: 99%